KAJIAN ENERGI SPESIFIK PADA BENDUNG BERTANGGA DENGAN VARIASI KEMIRINGAN HULU PADA SALURAN PERSEGI - Pamela Dinar Rahma; Suhudi, Suhudi; Maneek, Benyamin (Jurnal Qua Teknika, 2023)
Open channel flow is an open channel flow that is under the influence of the earth's gravity, the method used is the primary method that is measured, namely the water level, the speed of the froude number The purpose of the study is to determine the effect of water level, speed, froude number What is the specific energy in the presence of variations in the slope of the weir and know the effect of specific energy that occurs in each slope of the weir with variations in discharge, The results are as follows: Subcritical froude number flow type has no effect, the specific energy that occurs is: Q1 5.7435m, Q2 6.0225m and at Q3 6.3832m.